EMPLOYMENT POLICY IN REGIONS AND STRATEGIES FOR THE DEVELOPMENT OF HUMAN CAPITAL (American Journal of Business Management, Economics and Banking, 2025)
This article examines the employment policies implemented in various regions and their impact on the development of human capital. It explores strategic approaches aimed at enhancing workforce skills, improving labor market efficiency, and fostering sustainable regional economic growth. The study highlights the importance of coordinated policy measures to address regional disparities and promote inclusive employment opportunities that contribute to the overall advancement of human capital.